Wind Microturbine with Adjustable Blade Pitch Angle - Stanisław Chudzik (Energies, 2023)
The article presents the results of research on the operation of a wind microturbine model with an adjustable blade pitch angle. The physical basics of wind turbine operation and the methods of its optimal control are discussed. The results of the measurements carried out for the selected blade geometry with the possibility of adjusting the pitch angle are presented. The tests were carried out for a resistive load with a linear characteristic and for a load with a non-linear characteristic of a Li-Po battery. The results of the operation of a simple MPPT control algorithm are presented. The practical methods of controlling larger wind turbines are not optimal for small and very small turbines. The conducted research focused on determining the possibility of using blades with an adjustable angle setting, depending on the rotational speed in wind microturbines. The use of a simple mechanism for changing the pitch angle of the blades depending on the rotational speed of the turbine can increase the efficiency of the microturbine in a wider range of wind speeds.